Exploring Narrative through a Linguistic Lens: A Systematic Review of Critical and Theoretical Frameworks - Sinaga, Yanti Kristina; Matondang, Saiful Anwar; Manugeren, M (Universitas Pahlawan Tuanku Tambusai, 2025)
This paper presents a systematic review of scholarly literature published between 2015 and 2025 that explores narrative through a linguistic lens. The review aims to identify and synthesize major critical and theoretical frameworks applied to narrative studies within the field of linguistics. A total of 36 peer-reviewed studies were selected through comprehensive searches across major academic databases using keywords related to narrative linguistics, discourse analysis, and critical theory. The findings reveal four dominant categories of analysis: structuralist and formal linguistic frameworks, cognitive linguistic approaches, critical discourse analysis (CDA), and multimodal/digital narrative frameworks. While structuralist approaches focus on the formal organization of narrative elements such as syntax and coherence, cognitive frameworks emphasize the role of mental representation, conceptual blending, and embodiment in narrative comprehension. CDA-based studies investigate how narratives construct and challenge power relations, while multimodal approaches explore how meaning is shaped across verbal, visual, and digital modes. This review demonstrates a clear disciplinary shift toward integrative and socially responsive frameworks, reflecting the increasing complexity of narrative forms in contemporary communication. The study also identifies emerging gaps in cross-cultural perspectives and digital multimodal theory, suggesting directions for future research. By mapping recent developments in narrative theory from a linguistic standpoint, this paper contributes to a deeper understanding of how language constructs, conveys, and transforms stories across contexts.